Comparison of advanced oxidation processes for metaldehyde removal and downstream disinfection by-product formation - Diana, Marine (Cranfield University, 2017)
Metaldehyde is the pesticide that has been found to exceed the maximum regulatory concentration of 0.1 µg/L in drinking water the most in the UK in recent years. As a result of the pesticide not being removed by conventional water treatment processes, there has been an interest in alternative treatments including advanced oxidation processes (AOPs). The latter have been reported as promising technologies for the removal of recalcitrant micropollutants. A large scale pilot study was carried out to compare the performance of two different AOPs for removing metaldehyde from sources used to produce drinking water: the UV/H₂O₂ AOP and O₃/H₂O₂ followed by UV/H₂O₂ AOP. Since AOPs can increase the formation of disinfection by-products (DBP) under certain oxidation conditions, it is important to assess their impact on DBP precursors. For this purpose, the trihalomethane formation potential (THM FP) and the haloacetic acid formation potential (HAA FP) were measured upon chlorination of samples collected at different stages of the treatment. Both AOPs were shown to remove metaldehyde efficiently achieving removals of up to 98%. They were able to reduce metaldehyde concentration below the regulatory level with UV doses lower than 1 kWh/m³ for initial metaldehyde concentrations of up to 2.10 µg/L. Concentrations as high as this value can be found in sources used to produce drinking water. The O₃/H₂O₂ - UV/H₂O₂ AOP was up to 33% more efficient than the UV/H₂O₂ AOP when applied at UV doses lower than 0.60 kWh/m3. In this work, the electrical energy applied to the system was expressed in kWh/m³ to enable the comparison of both AOPs at similar operating conditions. Both AOPs either increased or decreased the THM FP and the HAA FP between -85% and +155% with respect to the inlet. However, the quality of the inlet water better explained these changes rather than the UV and oxidant doses applied.
Keywords: Hydroxyl radicals; micropollutant degradation; pilot study; trihalomethanes; haloacetic acids; natural organic matter; chlorination; UV/H₂O₂; O₃ /H₂O₂